PERAN PRODUSER SEBAGAI GATEKEEPER DALAM PROGRAM NEWS SCREEN DI IDX CHANNEL - Mutiah, Tuty (Jurnal Komunikasi, 2018)
The selection process of the producer as the gatekeepers in a program is very instrumental in a program. most of the mass media always want to display anything that has to do with this process, including the IDX Channel. As television affiliated with the Indonesia stock exchange, IDX Channel continue to strive to become the leading television in the world capital market information, including economic issues and business both National and international, one of them through the program news News Screen. In the process of the broadcast, all parties involved can act as gatekeepers, including producer. However, the role of producer as the gatekeepers in the process is important, this is due to the power and responsibility that the producer has during the process of the broadcast. the method of this Study about the role of producer as the gatekeepers is qualitative descriptive. From the results of the study turned out to be the final authority on structurally are in the hands of Executive producers who act as gatekeepers. however, in reality the newsancor was the one who did the final execution of news the content before it delivered to the society.Â key words : producers, gatekeeper, television program, idx channel